Identification of Ultraviolet (UV) Levels in the Caramelization Process of Sale Pisang - Berlianti, Rahmi; Kurniadi, Dedi; Putri, Dian Permata; Alfitri, Nadia; Susanti, Roza; Mudia, Halim (SOTVI, 2024)
Sale pisang is a typical Indonesian food made from dried bananas. Usually, this drying is done by drying directly in the sun. Drying bananas in the sun is not very effective because it takes a long time and is very dependent on weather conditions. After innovation was made by making a dryer, sale pisang was produced which had a hard texture and low moisture content that affected the caramelization process. Therefore, a dryer is needed that can replace the drying process under the sun. One of the contents of sunlight is ultraviolet light. Irradiation of ultraviolet light, especially UVC light, can help shrink the cell wall of bananas so that the evaporation of water during drying is small. This study aims to identify good UV levels for the caramelization process to produce the same sale pisang as drying under the sun using 5 different treatments, namely, without UV lighting, 15 minutes irradiation, 30 minutes irradiation, 1-hour irradiation, and 2 hours irradiation. Irradiation for 15 minutes produces a water content of 11%, irradiation for 30 minutes produces a water content of 12%, irradiation for 1 hour produces a water content of 18%, and Sale pisang with irradiation for 2 hours produces a water content of 20%. Based on the texture analysis produced by irradiation for 1 hour produces a texture that is almost the same as drying directly under the sun.